Laparoscopic cephalic pancreatectomy duodenum - García Alves, Alan; López, Gisela; Marani, Marcos; Alcaraz, Álvaro; Giordano, Enzo (Cirugía del Uruguay, 2022)
The laparoscopic approach to the pancreas is difficult due to its retroperitoneal location and complex vascular relationship. Adequate experience in conventional Whipple and laparoscopic skills are prerequisites to perform a laparoscopic cephalic-duodenal-pancreatectomy. Watch it at: https://youtu.be/5VgjtdIwA0Y